2015
DOI: 10.1111/ajr.12212
|View full text |Cite
|
Sign up to set email alerts
|

How effective and acceptable is Web 2.0 Balint group participation for general practitioners and general practitioner registrars in regional Australia? A pilot study

Abstract: Objective: General practitioners (GPs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 17 publications
0
37
0
1
Order By: Relevance
“…Eight studies [ 54 , 65 , 73 - 78 ] compared ODE with self-directed learning, which included no intervention or text-based learning. Of these, only four studies [ 65 , 74 , 76 , 78 ] had numerical information in a presentable format ( Figures 7 - 9 ). Five studies [ 65 , 73 - 76 ] reported that ODE was significantly more effective than self-directed learning (low certainty evidence).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies [ 54 , 65 , 73 - 78 ] compared ODE with self-directed learning, which included no intervention or text-based learning. Of these, only four studies [ 65 , 74 , 76 , 78 ] had numerical information in a presentable format ( Figures 7 - 9 ). Five studies [ 65 , 73 - 76 ] reported that ODE was significantly more effective than self-directed learning (low certainty evidence).…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in Australia confirmed the same [34]. Michael Balint also emphasized that an understanding of the patient’s inner world is central for a doctor’s insight.…”
Section: Discussionmentioning
confidence: 75%
“…a strong feature of this design is the social support that derives from discussion and sharing with fellow group members. an important intervention within this group of studies is the Balint Group, 29,43,44,50 which has its origin in the work of psychoanalysts Michael and edith Balint and employ a particular format for guided reflection. all of the interventions in this group of studies encompass elements of reflective discussion, with some also incorporating elements of small group learning.…”
Section: Reflective Groupsmentioning
confidence: 99%